DISTANCE IN SPLITTING AND COSPLITTING GRAPHS (International Journal of Engineering Sciences & Management Research, 2015)
The graph S(G) obtained from a graph G(V,E), by adding a new vertex w for every vertex v to all neighbours of v in G, is called the splitting graph of G. The cosplitting graph CS(G) is obtained from G, by adding a new vertex wi for each vertex vi and joining wi¬ to all vertices of G which are not adjacent to vi in G. In this paper, we study the properties related to distance in splitting and cosplitting graphs.